The guild and the swordsman - Chandler Jean (Bern Open Publishing, 2014)
Guilds have a well-established association with the fencing systems of medieval Europe, and the phenomenon of guilds has been the subject of a great deal of new academic research in the last 20 years or so. A thorough summary of the recent scholarship on guilds and their structure and history will help provide context for what may be loosely described as armed guilds. Though armed guilds have not yet been the subject of a proper systematic analysis, it is possible to tentatively identify four types. Combining the summary of 'civilian' guilds with the emerging evidence of armed guilds, including the fencing guilds, may help us better understand the social relevance of martial arts in medieval and Early Modern Europe. This may in turn contribute positively to the ongoing efforts to interpret the medieval fightbooks.